Betting on forever - Aronson, Billy; Quinn, John (New York : McGraw-Hill, 1996)
Strange-looking creatures from the past gather in their ghostly forms for an Extinct Animal Reunion where they discuss potential dangers to life on the planet.
Keywords: Extinct animals; Ecology; Wildlife conservation